Estudo fitoquímico das espécies Sida acuta e Sida linifolia (Malvaceae) e avaliação antitumoral de nanoemulsão contendo tilirosídeo - Sobreira, Ana Laura de Cabral (2023)
The use of medicinal plants since ancient times is the basis of the therapeutic system of different populations. In order to find the benefits, the natural products of the brassileira flora were explored through the phytochemical study of two species of the Malvaceae family, Sida acuta and Sida linifolia, carrying out a pioneering study of this last species. In addition to the phytochemical study, a nanoemulsion produced with tiliroside (kaempferol-3-O-β-D-(6”-E-p-coumaroyl)-glucopyranoside) dispersed had its antitumor efficacy evaluated. Extraction (maceration) and chromatography (column chromatography and analytical thin layer chromatography) were used to isolate the chemical constituents. The structural identification of the molecules was performed using 1H and 13C Nuclear Magnetic Resonance (1D and 2D), Mass Spectrometry (MS) and hyphenated techniques such as Liquid Chromatography coupled to Mass Spectrometry (LC-MS). The use of these techniques led to the isolation and identification of 4 secondary metabolites of Sida linifolia, including glycosylated flavonoids and aglycone. From the study of the hydroalcoholic phase by HPLC-ESI-MS/MS in both species, it was possible to identify 19 chemical constituents in Sida acuta and 11 compounds in Sida linifolia, which had their mass spectra analyzed by m/z and their fragments recorded. Among the compounds is tiliroside, considered by the research group a marker of the Malvaceae family. The O/W nanoemulsion produced by the phase inversion emulsification method and using tiliroside as active substance, macroscopically appeared slightly bluish, with a droplet diameter of 96 ± 9.06 nm and and polydispersion index 0.170 ± 0.01 after 60 days of storage at room temperature, in addition to a pH of 6.94 ± 0.08 and zeta potential of -10.1 ± 1.7 mV. The nanoemulsion with encapsulated tyliroside did not show promising anticancer activity against HL-60 (Acute Promyelocytic Leukemia), MCF-7 (Breast Adenocarcinoma) and SK-MEL-28 (Melanoma) cell lines at concentrations of 12.5; 25; 50 and 100 μg/ml. Despite this, it is necessary to deepen the exploration of the therapeutic potential and the formulation developed with tiliroside.